Equation of state for 1,1-difluoroethane (R152a) - Kim, Y; Borgnakke, C; Sonntag, RE (JOHN WILEY & SONS LTD, 1997)
A new equation of state (EOS) for 1,1,-difluoroethane (R152a) is developed in the form of the Helmholtz free energy. The EOS is valid for temperatures between 213 and 433 K (0.55 < T-r < 1.12) and pressures up to 20 MPa (P-r < 4.4). It covers EOS is valid for temperatures between 213 and 433 K (0.55 < T-4 < 1.12) and pressures up to 20 MPa (P-r < 4.4). It covers the compressed liquid, gas and two-phase regions, R152a, which does not contain any chlorine, is a potentially acceptable alternative refrigerant for chlorofluorocarbons. Chlorofluorocarbon compounds, which are widely used as refrigerants, propellants, foaming agents and cleaning agents, are known to damage the ozone layer that protects the Earth from harmful radiation, The form of the ideal gas Helmholtz free energy is obtained from statistical thermodynamics, and the residual part is determined from experimental data. From a bank of terms that are suggested, an optimum set of terms is selected by a random search method. The results are compared with the experimental data, and tables of the thermodynamic properties of R152a are presented. (C) 1997 by John Wiley & Sons, Ltd.
Keywords: LIQUID COEXISTENCE CURVE; 1,1,1,2-TETRAFLUOROETHANE R-134A; THERMODYNAMIC PROPERTIES; VAPOR-PRESSURES; HEAT-CAPACITY; R-152A; REFRIGERANTS; DENSITY; P,RHO,T; CFC